Corrosion of Carbon Steel Pipeline in Flow System of water Sweetening Plant - Atiya, Mohammed A.; Kadhim, Fadhil S. (Al-Khwarizmi Engineering Journal, 2008)
The electrochemical behavior of carbon steel in water sweetening station in Libya has been studied in the range of ( 293–333 oC) using weight loss technique. Measurements were carried out over a range of Reynolds number (5000 – 25000).An apparatus was designed for studying the corrosion process in the turbulent regime, which is of industrial significance. It was found that The corrosion rate of carbon steel in water sweetening station is under diffusion control and increases with increasing Reynolds number. On the other hand the variation of corrosion rate with temperature in the range of (293–333 oC) was found to follow Arrhenius equation and the activation energy approximately the same except at low Reynolds number.